How involved are parents in their child's early years setting's food decisions and practices? - Lorraine Williams; Emily Warren; Cecile Knai (Elsevier, 2022)
As childhood obesity and poor nutrition rates in England continue to rise, parents and childcare practitioners have key partnership roles in ensuring young children have healthy balanced diets. Yet little is known about parents' understanding and involvement in their childcare settings' food decisions and practices, and how this might be strengthened. Semi-structured interviews were carried out with a purposive sample of 59 parents with one or more children attending early years settings in England. Framework analysis was used to explore the interviews. Epstein's model of parental partnerships was adapted as a reflective lens for the findings, and their implication for early years' policy and practice. Parents reported a lack of two-way communication on food, and of opportunities for active, meaningful engagement around food and healthy eating outside of one-to-one discussions of their child's specific needs and requirements. Some parents reported a lack of trust in the food related information provided by their childcare setting. As young children spend more time in formal childcare, it is increasingly important that trusting collaborative relationships are built between parents and childcare practitioners to ensure that children have the best start in life. This study adds to the limited literature on parental involvement in early years settings. Findings suggest that more policy work and development is needed in the early years sector, particularly in ensuring clear and accessible guidelines on food in early years settings are readily available, and that practitioners and parents have more clarity about their mutual roles and responsibilities in this.